The Effect of Competence and Independence on Fraud Detection (Empirical Study at The West Java Representatives of The Audit Board of The Republic of Indonesia) - Nenden Indriani; Poppy Sofia Koeswayo; Cahya Irawady (Journal of Accounting Auditing and Business, 2022)
This research examines whether good auditor competence and independence affect fraud detection by the West Java representatives of the Audit Board of the Republic of Indonesia. The population in this research was the auditors of the West Java representatives of the Audit Board of the Republic of Indonesia. The purposive sampling technique was used to obtain 106 auditors of the Audit Board of the Republic of Indonesia. The data for this research were obtained from primary data through a questionnaire. Multiple. Linear regression analysis. It was used to analyze the data in the study. The regression. The coefficient of the competence variable indicates that the variable has a partially positive and significant effect on fraud detection. The regression. The coefficient of the independent variable suggests that the variable has partial and insignificant. Effect on fraud detection. Simultaneous hypothesis testing shows the competence and independence of the West. Java representatives. of the Audit. The Board of the Republic of Indonesia. have a significant and positive. Effect on fraud detection